Unpredicted transformation of acute myeloid leukemia with translocation (16;16) (p13; q22): a case report and review of the literature - Shams ElDoha Galal ElDin Zaiema; Heba Mohamed Saber Hafez (SpringerOpen, 2024)
Abstract Introduction The transformation of acute myeloid leukemia with translocation (16;16) (p13; q22) from AML M2 to acute monocytic leukemia (AML M5) during therapy is a rare clinical occurrence, and this is the first time it has been reported. Clinical complain A 19-year-old male patient was admitted for severe fatigue with anemic manifestation and weight loss, for more than 1 month, with exacerbation of the condition in the last 2 days. Diagnosis A primary diagnosis was made for AML M2 with t (16;16) (p13; q22) established on bone marrow (BM) morphology. A consequential detection of FLT-3 ITD mutation was done. At day 28 follow-up after induction and maintenance therapy, the diagnosis of AML M2 was maintained with a high bone marrow (BM) blast count, prompting the initiation of a more aggressive treatment protocol. After 1 month of implementing the recent protocol, the patient remains morphologically resistant with a notable transformation of bone marrow infiltration by an abnormal monocytic population (monoblasts and promonocytes). The final diagnosis of transforming FLT3-mutated AML with t (16;16) (p13; q22) was established. Intervention After the initial diagnosis of AML M2 with t (16;16) (p13; q22), the patient received the 3 + 7 induction protocol. The 2nd induction protocol initiated after the second evaluation and morphological resistance was the FLAG Adrian protocol. The 3rd protocol after transformation to AML M5 was 1 cycle of the MEC protocol. Anti-FLT3 treatment was considered. Outcomes The patient was maintained on the 3rd protocol of chemotherapy. Unfortunately, he was admitted to the ICU unit complaining of neutropenic fever and severe sepsis where he died before final re-evaluation and the anti-FLT3 treatment initiation. Conclusion AML with t (16;16) (p13; q22) characterized by favorable outcome. However, identifying additional chromosome abnormality or genetic aberration, especially FLT3 gene mutation, is recognized as an important factor influencing final disease outcome. Therefore, early detection of FLT3 mutations will allow comprehensive disease course prediction and targeted therapy that might achieve longer and more durable remissions.